The motivation of fixed orthodontic appliance patients with two-years of usage time - Widyandari, Paramita; Malik, Isnaniah; Sunaryo, Iwa Rahmat (Padjadjaran Journal of Dentistry, 2012)
Introduction: Motivation is the power that moves a person to behave, think, and feel like they do. The patient’s motivation when doing orthodontic treatment is essential to determine the success of the treatment. This study aimed to determine the description of the motivation of patients who have been using fixed orthodontic devices for two years at Dental Hospital Universitas Padjadjaran (RSGM Unpad). Methods: This type of research is done by using descriptive methods. The sampling technique is total sampling with the number of research samples obtained was 34 people. This research was conducted during October 2011. The type of patient motivation was determined by using a quartile in scoring the results of the questionnaire answers given to respondents, namely patients who came to the RSGM specialist integrated care facility. Patients’ motivation is categorized as very high, high, low, and very low. Results: The results showed that the majority of respondents were women, teenagers and young adults, with high school education and university students. Patient motivation levels obtained from data analysis were only very high and high categories in orthodontic treatment. Conclusion: All the respondents have a relatively high motivation for undergoing orthodontic treatment at the RSGM Unpad and no respondents who have low motivation.